Dynamic‐ and Light‐Switchable Self‐Assembled Plasmonic Metafilms. Issue 14 (30th April 2018) - Cormier, Sean; Ding, Tao; Turek, Vladimir; Baumberg, Jeremy J.
Abstract: Large‐area dynamic switchable plasmonic metafilms composed of a network of gold nanoparticles (Au NPs) and the thermo‐responsive polymer poly( N ‐isopropylacrylamide) (PNIPAM) are self‐assembled by casting Au@PNIPAM core–shell nanoparticles. These dense plasmonic films present an unusual optical behavior arising from the macroscale effective medium response of the film and the microscopic interactions of the gold nanoparticles. Such intensely colored plasmonic metafilms can be thermally actuated across large areas via direct heating, allowing extraction of the tuning of the effective dielectric permittivity of this metamaterial. By contrast, local plasmonic heating by illuminating the Au NPs in these metafilms enables sub‐second and highly reversible contraction of the plasmonic metafilms, capable of pumping water. This work provides a paradigm for switchable metafilms and metasurfaces that can be harnessed for different applications such as sensing, imaging optics, and image displays. Abstract : Large‐area Au@PNIPAM films show reversible tunability in reflectance by direct‐ and light‐induced heating of a few degrees Celsius. Combining the coil‐to‐globule phase transition of the thermo‐responsive polymer poly ( N ‐isopropylacrylamide) and the plasmonic properties of gold nanoparticles, a dynamic thin‐film coloration of a composite metallo‐dielectric metamaterial is demonstrated. Sub‐second switching rates are found for these plasmonic smart polymer composite films.